Photo Essay: On The Street - Hopper, John G. (1974)
When people speak of crime in the streets, they invariably refer to cold statistics or a report from a governmental agency as a source of information. There is however another source of information on the subject-that of personal experience. It is the unique experience that urban police sometimes refer to as being on the street . The following is this photographer's impression of spending several winter nights on the streets with an urban police force